Improved Self-Esteem in Artists After Participating in the “Building Confidence and Self-Esteem Toolbox Workshop” - Shack, Anita R.; Meiyappan, Soumia; Grossman, Loren D. (Frontiers in Psychology, 2018)
Performing and creative artists have unique occupational and lifestyle stresses and challenges that can negatively affect self-esteem. Low self-esteem not only has serious implications for their psychological and physical health, it can also affect their performance and creativity. There is a need to establish effective interventions to deal with this issue. To the best of our knowledge, there are no reported studies specific to workshops or interventions on enhancing self- esteem for artists. The Al and Malka Green Artists’ Health Centre at the Toronto Western Hospital, University Health Network, Toronto, Ontario, Canada, is a unique multidisciplinary and integrative clinic serving the special needs of the artist population. We developed a workshop entitled “Building Confidence and Self Esteem Toolbox Workshop” to address this this need. We then designed a single-blind, randomized, prospective, pilot study to evaluate the effectiveness of the workshop on enhancing self-esteem in artists, and to evaluate the long-term effectiveness of using the recommended tools in maintaining a healthy self-esteem, as well as maintaining physical and emotional health. Both quantitative and qualitative data were collected. A validated “Self-Esteem Checkup” questionnaire was administered pre- and immediately post workshop, as well as at 2, 6, and 12 months post workshop. Open-ended questions were posed to study participants via email at 2 and 12 months following the workshop, and at 6 months in in-person interviews. Thirty-five professional artists consented to participate in the study, with 26 completing all study visits. Mean scores for all time points, and the individual questionnaire statement mean scores for the five timepoints increased significantly immediately post-workshop and remained statistically significantly improved by the by the 3rd follow-up 12 months later. (p<0.001). The mean self-esteem rating score increased significantly post-workshop and remained statistically significantly improved by the 3rd follow-up 12 months later. (p<0.01). Qualitative data showed positive feedback on the utilization of the tools learned in the workshop that helped maintain this improvement over a one-year period. This workshop may be an effective means of addressing the issue of self-esteem in artists. Further controlled studies of larger sample size and longer duration are needed to confirm these findings.